Chitosan/arginine–chitosan polymer blends for assembly of nanofibrous membranes for wound regeneration - Antunes, Bernardo Paiva (2018)
Frequently, skin is subjected to damaging events, such as deep cuts, burns or ulcers, which may compromise the integrity of this organ. To overcome such lesions, different strategies have been employed. Among them, wound dressings aimed to re-establish skin native properties and decreased patient pain have been pursued for a long time. Herein, an electrospun membrane comprised by deacetylated/arginine modified chitosan (CH-A) was produced to be used as a wound dressing. The obtained results showed that the membrane has a highly hydrophilic and porous three-dimensional nanofibrous network similar to that found in human native extracellular matrix. In vitro data indicate that human fibroblasts adhere and proliferate in contact with membranes, thus corroborating their biocompatibility. This nanofiber-based biomaterial also demonstrated bactericidal activity for two bacterial strains. In vivo application of CH-A nanofibers in full thickness wounds resulted in an improved tissue regeneration and faster wound closure, when compared to non-modified membranes. Such findings support the suitability of using this membrane as a wound dressing in a near future.